Determination of Iron Content in Iron Deficiency Drugs by UV-Visible Spectrophotometer - Elgailani, Isam Eldin Hussein; Alamary, Hamdan Shoyaib (Orbital: The Electronic Journal of Chemistry, 2017)
The objective of this work was to validate a simple, precise and accurate spectrophotometric method for the determination of iron in the iron deficiency drugs, namely are Feroglobin B12, Ferose-F and Ferose. The proposed method is based on the reaction of iron with ammonium thiocyanate after the wet digestion of the drugs under study with HNO3 and H2O2. Effects of pH, temperature, standing time and thiocyanate concentration on the determination of iron in drugs containing iron have been investigated. The λmax was 430 nm and the molar absorptivity of 0.0399 L mol-1 cm-1. The linear regression was in the range 0.5 - 60 μg/mL for iron content in hemoglobin. The detection limit and the limit of quantification were found to be 0.040 and 0.122 µg mL-1 for the iron respectively, and with a linear regression correlation coefficient of 0.998. Recovery measurements ranged from 99.63-100.20%. This method is simple and fast can be used for the determination of iron in the iron deficiency drugs in pharmaceutical laboratories. DOI: http://dx.doi.org/10.17807/orbital.v9i3.953